2014
DOI: 10.2169/internalmedicine.53.3098
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin for the Treatment of Prostate Infection

Abstract: A 69-year-old man with diabetes mellitus was diagnosed with a prostate abscess. Although the pathogen was fluoroquinolone-resistant Escherichia coli and the oral administration of trimethoprim-sulfamethoxazole was initiated, the infection recurred after three months. The antibiotic therapy was subsequently changed to intravenous fosfomycin, and the patient's condition promptly improved. Four weeks of fosfomycin therapy was successfully continued without any adverse events. In the era of antibiotic resistance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Fosfomycin therapy in the complicated UTIs was, according to our data, ineffective in 51.3% of cases (i.e., the drug has no effect, or there is early relapse of symptoms within two months). In the treatment of complicated UTIs or UTIs caused by multidrug-resistant microbes, many studies suggested multiple dose regimens of fosfomycin [ 1 , 21 , 22 , 23 , 24 , 25 , 26 ] with three-dose regimens being the most common. Patients in our cohorts were mostly treated with a single-dose regimen; however, about one-third of them received multiple doses.…”
Section: Discussionmentioning
confidence: 99%
“…Fosfomycin therapy in the complicated UTIs was, according to our data, ineffective in 51.3% of cases (i.e., the drug has no effect, or there is early relapse of symptoms within two months). In the treatment of complicated UTIs or UTIs caused by multidrug-resistant microbes, many studies suggested multiple dose regimens of fosfomycin [ 1 , 21 , 22 , 23 , 24 , 25 , 26 ] with three-dose regimens being the most common. Patients in our cohorts were mostly treated with a single-dose regimen; however, about one-third of them received multiple doses.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial prostatitis is a disease that accounts for a quarter of all visits of men to urology clinics. Treating prostate infections is challenging due to the low penetration of antibiotics into prostatic tissues (Hagiya et al., ). The use of fluoroquinolones is recommended in cases of BP.…”
Section: Discussionmentioning
confidence: 99%